Bright and tender dark : a novel - Pearson, Joanna (Bloomsbury Publishing, 2024)
Decades after the murder of nineteen-year-old college student Karlie Richards, her former roommate, now middle-aged and divorced, becomes obsessed with uncovering the truth amidst online conspiracy theories, speculation and the lingering shadows of the past.